2015
DOI: 10.1007/7854_2015_418
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal 192 IgG-Saporin as Neuroteratogen

Abstract: The immunotoxin 192 IgG-saporin selectively destroys basal forebrain cholinergic neurons that provide cholinergic input to the hippocampus, entire cortical mantle, amygdala, and olfactory bulb. Perinatal immunotoxic lesions by 192 IgG-saporin induce long-lasting cholinergic depletion mimicking a number of developmental disorders reported in humans. The perinatal injection of 192 IgG-saporin induces several brain modifications, which are observed in neocortex and hippocampus at short and long term. These plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…To address this issue, in the present study we investigated whether a pre-treatment with n-3 PUFA was able to prevent behavioral and/or morphological deficits induced by basal forebrain cholinergic depletion in aged mice. The immunotoxic lesion of the basal forebrain through saporin provides a valid animal model to partially mimic AD pathology by provoking a selective and permanent removal of basal forebrain cholinergic inputs to the hippocampus, the entire cortical mantle, the amygdala and the olfactory bulb [13]. Overall, here we found that n-3 PUFA pre-treatment was effective in counteracting some functional and morphological deficits induced by the cholinergic depletion.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…To address this issue, in the present study we investigated whether a pre-treatment with n-3 PUFA was able to prevent behavioral and/or morphological deficits induced by basal forebrain cholinergic depletion in aged mice. The immunotoxic lesion of the basal forebrain through saporin provides a valid animal model to partially mimic AD pathology by provoking a selective and permanent removal of basal forebrain cholinergic inputs to the hippocampus, the entire cortical mantle, the amygdala and the olfactory bulb [13]. Overall, here we found that n-3 PUFA pre-treatment was effective in counteracting some functional and morphological deficits induced by the cholinergic depletion.…”
Section: Discussionsupporting
confidence: 51%
“…In the past three decades, the availability of saporin immunotoxins allowed studying the role of basal forebrain cholinergic system in several cognitive functions and its implications in aging and dementia [11][12][13]. In fact, saporin immunotoxins selectively cause death of cholinergic cells by inhibiting ribosomal protein synthesis when it is taken up into cells expressing the low-affinity p75 neurotrophin receptor [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…injection of the mu-p75-saporin (saporin) immunotoxin is a valid animal model to partially mimic early AD pathology in mice, since the loss of integrity of the basal forebrain cholinergic system is one of the most reliable hallmarks of AD pathology [53]. Namely, the saporin immunotoxin provokes a selective and permanent removal of basal forebrain cholinergic inputs to the hippocampus, the entire cortical mantle, the amygdala, and the olfactory bulb [54][55][56].…”
Section: Introductionmentioning
confidence: 99%